Solving the Cutting Stock Problem for a Steel Industry - ÜLKÜ, İLAYDA; TEKEOĞLU, UĞUR; ÖZLER, MÜGE; ERDAL, NİDA; TOLONAY, YAĞIZ (Springer-Verlag Singapore Pte Ltd., 2022)
The problem of stock cutting takes an important place in the steel industry, as it is in many sectors. It is desired to ensure a minimum amount of waste in every manufacturing factory. Reaching the minimum level of waste reduces the costs of factories and companies and strengthens the possibility of making profits. In this way, it is ensured that our resources are used correctly in our developing world. In this study, the Cutting Stock Problem has been handled, in order to minimize the amount of waste within the scope of the complete the study and to solve this problem. In this study, first of all, the size of the steel to be used in line with the customer's request, the process of taking the steel plates from the stock and the molds of the parts to be cut are prepared by the production planning department, and these operations are carried out with the program used in the factory. Then the dies are sent to the workshop for cutting, where they are cut. Before creating the model, the data of the molds made for the previous cut are collected. In order to create the correct mathematical model, the data are collected by making simultaneous measurements at the cutting table. The cutting Stock Problem is used to formulate the molds prepared for cutting and the amount of waste loss is calculated. Determined parameters and constraints GAMS software is used to create a mathematical model using the GAMS MIP (Mixed Integer Programming) method and then analyze the created model. As a conclusion, we investigated 3 different scenarios. According to those experiments, the study with the proposed scenario can achieve a better production line especially about time and waste amount. Those developments can be important earnings for a real production line.
21st International Symposium on Production Research (ISPR) - Digitizing Production System
▪ Part of the Lecture Notes in Mechanical Engineering book series (LNME).
Keywords: Cutting Stock Problem; Mathematical Modelling; Mixed Integer Programming